2021
DOI: 10.1177/21582440211016553
|View full text |Cite
|
Sign up to set email alerts
|

Using Production-Oriented Approach in Business English Courses: Perceptions of China’s English-Major and Non-English-Major Undergraduates

Abstract: In light of pedagogical innovation, this study reports a two-stage survey with 172 participants from English-major and non-English-major programs on their needs of production-oriented approach and perceptions of effective implementation strategies in business English courses at a Chinese university. The results of the study suggest that while the two student groups used different learning methods, both valued communication with native speakers. While the two groups had different needs in business English readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…English writing (Yin, 2019;Du, 2022;Liu, et.al., 2020 (Balázs, 2020;Li et al, 2022;Qiu, 2020;Sun, 2020;Xie, 2021;Yang, 2022) "Autonomous learning" (J. Shu, 2022) "Students' motivation" (Li et al, 2022;Ren & Wang, 2018) "Enthusiasm for English learning" (X.Wang, 2022) "Critical thinking skills" (Lei & Mokhtar, 2023;X. Liu, 2021) A majority of studies targeted micro English skills such as reading, writing, speaking, translation, interpreting, and grammar.…”
Section: Targets Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…English writing (Yin, 2019;Du, 2022;Liu, et.al., 2020 (Balázs, 2020;Li et al, 2022;Qiu, 2020;Sun, 2020;Xie, 2021;Yang, 2022) "Autonomous learning" (J. Shu, 2022) "Students' motivation" (Li et al, 2022;Ren & Wang, 2018) "Enthusiasm for English learning" (X.Wang, 2022) "Critical thinking skills" (Lei & Mokhtar, 2023;X. Liu, 2021) A majority of studies targeted micro English skills such as reading, writing, speaking, translation, interpreting, and grammar.…”
Section: Targets Studiesmentioning
confidence: 99%
“…The other studies targeted English translation (Qi, 2022), interpreting (Guo, 2020), and grammar (Zhang & Choe, 2020) in a general view without a specific description of each skill. Five studies (Balázs, 2020;Li et al, 2022;Qiu, 2020;Sun, 2020;Xie, 2021;Yang, 2022) targeted students' global English proficiency by designing POA modules. Most of them examined the effect of pre-post tests on students' English level and generally reported a positive effect of POA on students' EFL academic level.…”
Section: Targets Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…e research results indicated that the application of POA theory was of great significance for the reform and theoretical development of business English teaching in Chinese universities and for further innovation and improvement of the teaching process in other cultural and educational contexts [8].…”
Section: Introductionmentioning
confidence: 99%
“…"It is the driving force and support for accelerating China's progress from a big educational country to an educational power [2]. Professional orientation curriculum is arbitrary and lacks planning and systematicness, while scientific and pragmatic business English curriculum is very necessary and positive [3]. In the exploration and practice of business English education and teaching, some problems that need to be solved urgently and are difficult to solve have been exposed.…”
Section: Introductionmentioning
confidence: 99%